ANALISIS KINERJA KREDIT MIKRO SEGMEN AGRIBISNIS DI PT BANK RAKYAT INDONESIA Tbk CABANG MUNTILAN - , RISMARINDA SEKAR TUNJUNG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to understand: (1) total performance of micro-credit and microsegment of Agribusiness in BRI Muntilan that consists of outstanding and NPL, (2) micro-credit proportion in agribusiness segment, (3) customer micro-credit performance in agibusiness segment in BRI Muntilan, and (4) the effort from BRI to overcome NPL. Descriptive analytical method was used in this study. Primary data was gained by random sampling among micro-creditâs customer from 12 fields of BRI Muntilan. In this research, secondary data was obtained as business development and Micro-credit report of BRI Muntilan per economic sectors and business segments presented monthly from 2011 until 2013. The results showed that overall outstanding micro-credit in BRI Muntilan progression up and NPL (non performing loans) has decreased and in the level of development of the good that is less than 5%. Performance customers micro-credit segment of agribusiness BRI Muntilan insecurity good by 95% customers included in category of good, effective and credit smoothly. Agribusiness segment micro-credit has the proportion of 65% of the total amount of micro-credit. Efforts BRI Muntilan in overcoming NPL is by giving socialization to rural communities, giving directives credit when filing credit, do the observation and visit the relationship to potential customers in order, to give time to repay a loan, the credit restructuring and finished with the family.